Biological activities and nitrogen and phosphorus removal during the anabaena flos-aquae biofilm growth using different nutrient form. (March 2018) - Zhu, Yuxuan; Tu, Xiaojie; Chai, Xin-Sheng; Wei, Qun; Guo, Lina
Highlights: An anabaena flos-aquae biofilm based on elastic polyvinyl chloride carrier. The biological activities in the anabaena flos-aquae biofilm growth was very high. Ammonium chloride was better N sources for the anabaena flos-aquae . Dipotassium hydrogen phosphate was better P sources for the anabaena flos-aquae . The anabaena flos-aquae biofilm can removed the N and P contaminates effectively. Abstract: This work investigated the biological activities and nitrogen and phosphorus removal during the anabaena flos-aquae biofilm growth on the polyvinyl chloride (PVC) carriers, in different nutrient form mediums. The study showed that the production of dehydrogenase activity (DHA) and extracellular polymeric substances (EPS) can reach 40.4 g/(h·m 2 ) and 115 × 10 −2 g/m 2 in an 11-day period, respectively, indicating that the anabaena flos-aquae biofilm had high biological activities. The results showed that the nitrogen and phosphorus removal reached 94.9 and 96.8%, respectively, in the ammonium form nitrogen group; while 97.7% of phosphorus were removed in the orthophosphate form phosphorous group. A comparison study was conducted and results showed that the present anabaena flos-aquae based biofilm provided a better removal of nitrogen and phosphorus than the other microalgae biofilms.